The interpreter's Bible ; v. 1 the Holy Scriptures in the King James and Revised Standard versions with general articles and introduction, exegesis, exposition for each book of the Bible in twelve volumes. - Buttrick, George Arthur, 1892-1980 (Nashville, TN Abingdon, 1952)
Contents : v.1 : General articles on the Bible; General articles on the Old Testament; Genesis, Exodus. Includes bibliographical references, maps.
Keywords: Bible -- commentaries